PERSEPSI PERAWAT DALAM PENERAPAN BUDAYA KESELAMATAN PASIEN DI RS X KOTA MALANG - Elystia Vidia Marselina; Chyntia Vicky Alvionita (Jurnal Rekam Medis dan Informasi Kesehatan Indonesia, 2024)
The quarterly report in 2022 shows that the incidence rate is not expected to reach 99 cases. One effort that can be made to prevent patient safety incidents is to implement a patient safety culture. Nurses as health workers who interact most with patients are the main component who are required to carry out their work in accordance with standard operational procedures to avoid patient safety incidents. Perception is very important in the success of communication, when all nurses have the same perception about the importance of implementing patient safety culture then patient safety incidents can also be prevented. The aim of this research was to measure nurses' perceptions of patient safety culture. The research instrument used a questionnaire based on the HSOPSC which was distributed to 55 nurses as research respondents. This type of research uses descriptive analysis to describe 12 dimensions of patient safety culture. The results show that the cooperation dimension within the unit has the highest positive perception, namely 87% in the good category, while the staffing dimension has the lowest positive perception, namely 61% in the medium category. RS X Kota Malang in its commitment to preventing patient safety incidents can focus on staffing dimensions.